Vertical Gardening Practices for Environmental and Socioeconomic Wellbeing: A Study on Mirpur DOHS of Dhaka City - Rahman, Md. Habibur; Rahman, Md. Mizanur (The Jahangirnagar Review, 2024)
The capital city of Bangladesh, Dhaka is losing its green facade day by day and it is affecting our urban eco-systems. It produces multi-dimensional socio economic, cultural and environmental problems. To mitigate these urban problems, vertical garden could be a solution. Vertical garden and/or rooftop garden has its diverse uses like reducing the hostile ecological effect of the buildings, greenhouse gas emission and to some extent regulating the temperature. Therefore, the present study aims in evaluating the contemporary practices of vertical gardening and its contribution in disaster risk reduction in the context of the Mirpur DOHS of Dhaka city. The study followed both quantitative and qualitative approach using questionnaire survey, in-depth interviews, observation and visual documentation as data collection tools for identifying the contemporary practicing types of vertical gardening. Research shows the most common types of plants in Mirpur DOHS area which are cultivating throughout the year. This study attempts to review the way vertical gardening reduce urban disaster risk. The preliminary findings suggest that vertical gardening can be the source of urban food security and improving the quality of the living environment. Practicing sustainable farming, urban territory can be benefited environmentally, socially and economically. Finally, some suggestions are addressed to improve practice of vertical gardening in the near future.